Role of terms of trade in Indian agricultural growth: a national and state level analysis - Hazell, Peter B. R.; Misra, V. N.; Hojjati, Behjat (International Food Policy Research Institute, 1995)
Using time series data, this paper analyses the relative contributions of terms of trade and non-price variables in explaining agricultural growth in recent decades in India. Agricultural growth is largely explained by expansion of irrigation, (which in the model is also a proxy for HYVs and other capital investments), and, until the 1970s, by increases in the net cultivated area. Agricultural output is inelastic, and is becoming increasingly more so over time. The terms of trade was not an important factor in explaining past growth. Even during the late 1960s and early 1970s when the terms of trade improved by 18 percent for agriculture, they only accounted for 15 percent of the growth in output. Increases in agricultural output are also found to worsen the terms of trade for agriculture, despite government attempts to control prices. The results highlight the importance of further investments in agricultural research, extension, irrigation and other supply-enhancing inputs if the ongoing policy reforms in India are to translate into more rapid and sustained agricultural growth.